Nevyriausybinių organizacijų ir JUNESKO bendradarbiavimas bibliotekininkystės srityje - Macevičiūtė, Elena (Knygotyra, 1985)
The article deals with the main international organizations of librarians and their relations with UNESCO which nowadays plays the role of the main coordinator and organizer of the international cooperation in librarianship. The author presents and characterizes the main nongovernmental organizations IFLA, FID, ICA, ISO, ICSU taking part in the activities of the library and information work and UNESCO itself. The main trends in the cooperation among these organizations are traced in the article from 1946. The understanding that the problems of information, librarianship and documentation must be solved in common was developed during this period. It has led to closer relations of organizations, to founding the Liaison Committees and mutual creation and participation in the international programmes of information and library work. The practice of the cooperation among international organizations may in some respect be useful in solving the problems of interlibrary and intersystem cooperation in our country.